2021
DOI: 10.1038/s41598-021-81952-8
|View full text |Cite
|
Sign up to set email alerts
|

Gene co-expression network analysis reveals immune cell infiltration as a favorable prognostic marker in non-uterine leiomyosarcoma

Abstract: The present study aimed to improve the understanding of non-uterine leiomyosarcoma (NULMS) prognostic genes through system biology approaches. This cancer is heterogeneous and rare. Moreover, gene interaction networks have not been reported in NULMS yet. The datasets were obtained from the public gene expression databases. Seven co-expression modules were identified from 5000 most connected genes; using weighted gene co-expression network analysis. Using Cox regression, the modules showed favorable (HR = 0.6, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…KLRB1 (killer cell lectin-like receptor B1) is a surface marker produced by the vast majority of T cell subsets that can signify innate immunity ( 45 , 46 ). Several studies ( 45 , 47 , 48 ) found that it had a possible prognostic value for good survival in non-uterine leiomyosarcoma and BC, which was consistent with our results that KLRB1 had a protective function in BC. BIRC3 (baculoviral IAP repeat-containing 3) belongs to the apoptosis inhibitor family ( 49 ).…”
Section: Discussionsupporting
confidence: 93%
“…KLRB1 (killer cell lectin-like receptor B1) is a surface marker produced by the vast majority of T cell subsets that can signify innate immunity ( 45 , 46 ). Several studies ( 45 , 47 , 48 ) found that it had a possible prognostic value for good survival in non-uterine leiomyosarcoma and BC, which was consistent with our results that KLRB1 had a protective function in BC. BIRC3 (baculoviral IAP repeat-containing 3) belongs to the apoptosis inhibitor family ( 49 ).…”
Section: Discussionsupporting
confidence: 93%
“…Knockdown of KDM1A promoted the ferroptosis sensitivity of lung cancers. The analysis of gene co-expression network is an outstanding approach for identifying the co-expression patterns of candidate genes in different phenotypes, and has been widely used for gene function annotation 22,23 . The co-expressed genes of KDM1A (Table S2) were downloaded from a lung adenocarcinoma dataset, TCGA Pan-Cancer Atlas, to further evaluate the underlying mechanisms regulated by KDM1A co-expression molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Although this study identified both functional modules and regulatory relationships between individual gene pairs, most other studies only reported functional modules of cancers using co-expression analysis [17][18][19]. In addition to using the CC for the estimation of GCNs, some modifications are applied for better estimation of co-expression relationships [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Weighted gene co-expression analysis (WGCNA) is one of the most widely used methods.…”
Section: ( )mentioning
confidence: 99%